PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA DIABETES MELITUS TIPE II - Luluk Cahyanti; Devi Setya Putri; Alvi Ratna Yuliana; Vera Fitriana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
ABSTRACT Background: Type II Diabetes Mellitus or commonly called lifestyle diabetes is diabetes caused by an unhealthy lifestyle. In someone with type II diabetes mellitus, insulin can still be produced by the pancreas, but the amount of insulin is still insufficient so that type II diabetes mellitus is considered as NIDDM (Non Insulin Dependent Diabetes Mellitus). IDF estimates that there are 463 million people in the world experiencing diabetes mellitus in 2019. There has been an increase in the incidence of diabetes mellitus by 19.9% ​​in 2020. In Central Java in 2019 there were 13.4% new cases of diabetes mellitus. Data from the Kudus Regency Health Office in 2019 noted that 17,869 people had diabetes mellitus, especially at the UPTD health centers in Japan, as many as 1,210 people had diabetes mellitus in 2022. There are 4 pillars in the management of DM, such as education in the form of knowledge about DM, regulation/diet in the form of low carbohydrates, pharmacological therapy in the form of Oral Hyperglycemic Drugs (OHO), and physical exercise, one of which is progressive muscle relaxation therapy. The purpose of this study was to determine the effect of progressive muscle relaxation therapy on reducing blood glucose levels in diabetes mellitus. The design in this study was pre-experimental, with a one-group pre-test and post-test design approach. There are two variables, namely the independent variable giving Progressive Muscle Relaxation Therapy while the dependent variable is Blood Glucose Levels in Type II Diabetes Mellitus. The population is all patients with Diabetes Mellitus in the working area of ​​the Kudus Japan Health Center in 2022 as many as 1210 people. Taken by purposive sampling technique. Collecting data using a questionnaire and checklist. Data analysis techniques using SPSS with the Wilcoxon statistical test. The Asimp.Sig result is 0.000 <0.05, then H0 is rejected, meaning that there is an effect of progressive muscle relaxation therapy. The purpose of this study was to determine the effect of progressive muscle relaxation therapy on reducing blood glucose levels in diabetes mellitus II. Respondents who used it experienced a decrease in GDS after being given progressive muscle relaxation therapy 84.7% greater than before being given the action. For this reason, it is necessary to provide progressive muscle relaxation therapy to reduce blood glucose levels in diabetes mellitus II.